Developing and engaging clinical leaders in the "new normal" of hospitals : why it matters, how to do it - Lega, Federico; Pirino, Angela (Emerald Publishing Limited, 2022)
Healthcare systems across the globe are currently facing perhaps the greatest challenges and pressures to date as the need to improve outcomes, efficiency, productivity, quality, customer satisfaction and sustainability have significantly risen. Further, the emerging focus on value-based healthcare has increased performance expectations. To improve capability to face these challenges, doctors were "transformed" by health organizations and systems into more hybrid figures, i.e., doctor-managers and most recently clinical leaders. Yet, in many cases their engagement hasn't worked as expected or desired, and there is still much ambiguity on what is the set of expectations attached to the new hybrid role. Providing a systematic review of previous literature about the progressively worrying challenge in transforming doctors to clinical leaders, Lega and Pirino offer a qualitative analysis of different advanced countries facing the issue of training this hybrid role. Finding improved practices applicable elsewhere, they conclude with a case study focus on the Italian system. Developing and Engaging Clinical Leaders in the "New Normal" of Hospitals suggests specific policy and practice recommendations on how the system should evolve with regards to clinical leadership.
Keywords: Health services administration.; Hospitals -- Administration.; Medical -- Hospital Administration & Care.; Medical administration & management.; elektronické knihy; electronic books